The Role of the Z-DNA Binding Domain in Innate Immunity and Stress Granules - Chiang, De Chen; Li, Yan; Ng, Siew Kit (Frontiers in Immunology, 2021)
Both DNA and RNA can maintain left-handed double helical Z-conformation under physiology condition, but only when stabilized by Z-DNA binding domain (ZDBD). After initial discovery in RNA editing enzyme ADAR1, ZDBD has also been described in pathogen-sensing proteins ZBP1 and PKZ in host, as well as virulence proteins E3L and ORF112 in viruses. The host-virus antagonism immediately highlights the importance of ZDBD in antiviral innate immunity. Furthermore, Z-RNA binding has been shown to be responsible for the localization of these ZDBD-containing proteins to cytoplasmic stress granules that play central role in coordinating cellular response to stresses. This review sought to consolidate current understanding of Z-RNA sensing in innate immunity and implore possible roles of Z-RNA binding within cytoplasmic stress granules.